Pendugaan Produksi Padi Dengan Menggunakan Citra Landsat 8 di Kabupaten Tabanan - SINAGA, FERNANDO JOSUA; NUARSA, I WAYAN; SARDIANA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.1, Januari 2020, 2020)
Estimation of Rice Production Using Landsat 8 Satellite in Tabanan District Agricultural sector is currently a very important sector considering that every human being needs food to survive and as a source of energy to carry out daily activities. Production estimation that are accurate and timely can provide information for planners and decision-makers to formulate appropriate policies when conditions are inadequate or overstocked. The technology that can be used is remote sensing using the Landsat 8 satellite. The greenness level parameters of plants (Vegetation Index) obtained through satellite image analysis can be used to estimate rice production. The research area is located in Tabanan Regency. Estimation of rice production is done by the equation y = 2.0442e1.8787x, where x is the NDVI value from the Landsat 8 image and y is the result of rice production. The estimation results using Landsat 8 are one season production in tons/ha. The accuracy test is done by paired t-test and correlation analysis. Paired t-test shows that there are no significant differences between rice production estimation from BP3K and rice production estimation using Landsat 8. Correlation analysis results show that there is a linear relationship between statistical results and estimation results with R2value 0.9682 with the equation y = 1.0099x - 0.0794, where y and x are Landsat 8 estimates in tons/ha and BP3K data respectively, with a Standard Error (SE) of 0.1984.